1982
DOI: 10.1007/bf00293350
|View full text |Cite
|
Sign up to set email alerts
|

Anther culture of wheat (Triticum aestivum L.) F1's and their reciprocal crosses

Abstract: Anthers from three sets of wheat (Triticum aestivum L. em. Thell) F1's and their reciprocal crosses, made between parental lines differing greatly in their ability to produce microspore derived callus, were cultured on the Chinese potato medium so that we could 1) more clearly define the role of nuclear or cytoplasmic factors within T. aestivum in transferring the ability to undergo in vitro androgenesis, and 2) to briefly review the gametic representation and disease screening potential of the resulting polyh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(27 citation statements)
references
References 3 publications
5
22
0
Order By: Relevance
“…The genetic data show that regenerating embryos come from different microspores (Bullock et al 1982). Rarely, however, coalescent embryos regenera ting two different plants can be observed .…”
Section: Factors Of Embryo Regeneration Abilitymentioning
confidence: 94%
See 3 more Smart Citations
“…The genetic data show that regenerating embryos come from different microspores (Bullock et al 1982). Rarely, however, coalescent embryos regenera ting two different plants can be observed .…”
Section: Factors Of Embryo Regeneration Abilitymentioning
confidence: 94%
“…In one case the hybrid was worse than the mid-parent value. In some cases Fl are intermediate between the two parents (Bullock et al 1982). …”
Section: General Possibilitiesmentioning
confidence: 94%
See 2 more Smart Citations
“…In wheat plants regenerated from pollen, a large percentage ofregenerates are albino (1), and this albinism has been clearly shown to be caused by massive chloroplast DNA deletions (6). We initiated these studies to establish ifa similar phenomenon was causing the albinism observed in some hypohaploid phenotypes ofN.…”
mentioning
confidence: 99%